2011
DOI: 10.1002/jhm.928
|View full text |Cite
|
Sign up to set email alerts
|

Treating alcohol withdrawal with oral baclofen: A randomized, double‐blind, placebo‐controlled trial

Abstract: BACKGROUND:Abrupt cessation of alcohol intake causes habituated drinkers to experience symptoms of alcohol withdrawal syndrome (AWS).OBJECTIVE:To determine the effect of the gamma‐aminobutyric acid (GABA)‐B agonist baclofen on the course of acute symptomatic AWS.DESIGN:Prospective, randomized, double‐blind, placebo‐controlled clinical study.SETTING:Two tertiary‐care hospitals in Duluth, Minnesota.PATIENTS:Inpatient adults admitted for any reason (including AWS) judged to be at high risk for AWS.INTERVENTION:In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…Despite the positive results obtained in this single study, evidence for recommending baclofen in the treatment of AWS was considered insufficient by the authors of the review. A subsequent RCT confirmed the effectiveness of baclofen compared to placebo in reducing the intensity of AWS [83]. Namely, this study, in which all subjects received symptom-triggered benzodiazepines, found that baclofen reduced the use of benzodiazepines in the management of AWS over 72 h of observation (table 2).…”
Section: Baclofen and Sudsmentioning
confidence: 65%
See 3 more Smart Citations
“…Despite the positive results obtained in this single study, evidence for recommending baclofen in the treatment of AWS was considered insufficient by the authors of the review. A subsequent RCT confirmed the effectiveness of baclofen compared to placebo in reducing the intensity of AWS [83]. Namely, this study, in which all subjects received symptom-triggered benzodiazepines, found that baclofen reduced the use of benzodiazepines in the management of AWS over 72 h of observation (table 2).…”
Section: Baclofen and Sudsmentioning
confidence: 65%
“…In fact, these articles described 11 RCTs because 2 of them referred to the same RCT [76,77]. In detail, 4 RCTs were on AUDs [73,74,75,80], 2 RCTs were on the treatment of withdrawal from alcohol or other substances [76,77,83], 2 RCTs were on the treatment of CUDs [82,84], 1 RCT was on the treatment of opioid use disorders [78], 1 RCT was on the treatment of nicotine use disorders (NUDs) [79] and the last RCT was on the treatment of methamphetamine use disorders [81]. Details of these RCTs are shown in tables 1, 2, 3.…”
Section: Baclofen and Sudsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbamazepine and gabapentin have proven comparable to benzodiazepines in several studies (29,30). Valproic acid and baclofen have been used adjunctively to decrease the administration of benzodiazepines and improve subjective withdrawal symptoms (31,32). A single dose of the older anticonvulsant phenobarbital in the ED may improve outcomes and facilitate outpatient detoxification (33,34).…”
Section: How Would You Stabilize This Patient?mentioning
confidence: 99%